Copyright Is a Joke: Perspectives on Joke Theft in Stand-Up Comedy, and How To Save the Punchline - Hopper, Jared B. (The Columbia Journal of Law & the Arts, 2024)
It seems that while comics are interested in using the law to enforce joke theft, no legal mechanism currently exists that would apply in a meaningful way to the intangible and ever-changing nature of performed comedic material. Perhaps the realities of the stand-up comedy industry are incompatible with a purely legal solution, and it would be better to get creative, break down the norms-based system, and determine how best to import components of legal redress in a way that not only preserves the efficacy of the current approach but also addresses some of the pitfalls leading to inconsistent enforcement. In attempting to bolster the protections against joke theft while respecting the preferences of comedians, learning from the law might be better than leaning on the law.